PENGARUH PERSEPSI KUALITAS DAN CITRA MEREK TERHADAP LOYALITAS PELANGGAN DENGAN KEPERCAYAAN PELANGGAN DAN KEPUASAN PELANGGAN SEBAGAI VARIABEL ANTARA - Faizal, Hanim; Nurjanah, Siti (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
The objective of this research is to know the effect of perceived quality, brand image towards customer loyalty through customer trust and customer satisfaction as intervening variables. The research model is the quantitative approach through a survey of 170 Mazda customers across 17 Dealers in Java, Kalimantan & Sulawesi. The sampling method is purposive sampling. The hypothesis test result shows that there is significant effect between perceived quality and brand image towards customer trust. And there is significant effect between perceived quality and brand image towards customer satisfaction. There is no significant effect between perceived quality towards customer loyalty and there is no significant effect between customer trust towards customer loyalty. But there is significant effect between brand image towards customer loyalty and there is significant effect between customer satisfaction towards customer loyalty. Based on the result, the company need to do marketing strategies by using 6P’s (People, Payplan, Product, Price, Place, Promotion) in order to enhance the positive impression of perceived quality and build customer trust through marketing activities to make a customer loyal to use Mazda car in Indonesia. Keywords: perceived quality, brand image, customer trust, customer satisfaction, customer loyalty